Hypoxic targeting and activating TH-302 loaded transcatheter arterial embolization microsphere. (1st January 2020) - Ma, Pengkai; Chen, Jianhua; Qu, Haixian; Li, Ye; Li, Xiaohui; Tang, Xuemei; Song, Zhigang; Xin, Hainan; Zhang, Jinbang; Nai, Jingxue; Li, Zhiping; Wang, Zhijun
Abstract: The tumor-derived and transcatheter arterial chemoembolization (TACE) induced hypoxia microenvironment is closely related to the poor prognosis of hepatocellular carcinoma (HCC). In this study, hypoxia-activated prodrug TH-302 loaded poly(lactic-co-glycolic acid) (PLGA)-based TACE microspheres were prepared to treat HCC through localized and sustained drug delivery. TH-302 microspheres with three different sizes were fabricated by an oil-in-water emulsion solvent evaporation method and characterized by scanning electron microscopy (SEM), infrared spectra (IR), X-ray diffractometer (XRD), and drug release profiles. The in vitro antitumor potential was firstly evaluated in an HepG2 cell model under normoxic and hypoxic conditions. Then, a VX-2 tumor-bearing rabbit model was established and performed TACE to investigate the in vivo drug tissue distribution and antitumor efficiency of TH-302 microspheres. Blood routine examination and histopathological examinations were also conducted to evaluate the safety of TH-302 microspheres. TH-302 microspheres with particle size 75–100 μm, 100–200 μm, and 200–300 μm were prepared and characterized by sphere morphology and sustained drug release up to 360 h. Compared with TH-302, the microspheres exhibited higher cytotoxicity, cell apoptosis, and cell cycle S phase retardation in HepG2 cells under hypoxic conditions. The microspheres also displayed continuous drug release in the liver tissue and better anti-tumor efficiency compared with TH-302 injection and lipiodol. Meanwhile, no serious toxicity appeared in the duration of treatment. Therefore, TH-302 microspheres showed to be feasible and effective for TACE and hold promise in the clinical for HCC chemoembolization therapy.